(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Theories of nations and nationalism consider language as one of the important factors that define the basis of a nation. The language dispute between Bulgaria and Macedonia is not a recent issue. In its very sharp form it exists since the second half of 19th century when the two views were determined: one which embraced a common linguistic standard for Macedonians and Bulgarians; and the position of the so called makedonisti, who insisted that a separate linguistic development for Macedonian nation must be introduced. With the codification of the Macedonian linguistic standard in 1944, the language dispute with Bulgaria reached another dimension. Following the proclamation of the Macedonian Independence and their recognition by Bulgaria in 1992, a number of contracts of mutual cooperation remained unsigned due to the linguistic dispute. A breakthrough was made in 1999 when the Declaration for Good Neighbourship was signed in Macedonian language in accordance with the Constitution, and Bulgarian language in accordance with the Bulgarian Constitution, and a formulation which was also accepted when the Treaty of Good Neighbourship was signed in • The purpose of this paper is to use the historical and explicative approach to explain the genesis of Bulgarian - Macedonian language dispute, especially its escalation following the codification of the Macedonian standard language in 1944/1945. Analysis was performed with the comparative approach, which included analogies with other national linguistic contexts for the unsustainability of the Bulgarian thesis for non-existence of an independent Macedonian language. A special review was carried out due to the dilemma on whether the formulation from the Treaty “Language in accordance to the Constitution” was Bulgaria’s attempt to devalue and deny the autochthony of the Macedonian language as an important marker of the Macedonian nation.